Women and liveability – best practices of empowerment from Malaysia - Amriah Buang,; Suryandari, Ratnawati Yuni; Habibah Ahmad,; Kaseh A. Bakar,; Hamzah Jusoh,; Hazita Azman, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
How to survive and make ends meet and how to improve the quality of life are daily and persistent livelihood issues and liveability challenges preoccupying disadvantaged communities in underdeveloped and developing countries. Even in politically stable Malaysia life struggles could be complex and challenging for womenfolk who more often than not are left on their own to cope with daily liveability problems. Through examining the findings from secondary information sources this paper illustrates three cases of how women helped make the best of empowerment projects geared to make the livelihood and liveability of themselves, their family and community better and more meaningful. It also highlights the institutional and organizational traits that were the success factors of the empowerment projects.